2016
DOI: 10.1155/2016/2584940
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA Methylation of MicroRNA Genes in Temporal Cortex from Alzheimer’s Disease Individuals

Abstract: This study investigated for the first time the genomewide DNA methylation changes of noncoding RNA genes in the temporal cortex samples from individuals with Alzheimer's disease (AD). The methylome of 10 AD individuals and 10 age-matched controls were obtained using Illumina 450 K methylation array. A total of 2,095 among the 15,258 interrogated noncoding RNA CpG sites presented differential methylation, 161 of which were associated with miRNA genes. In particular, 10 miRNA CpG sites that were found to be hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…In particular, a significant increase in FasL mRNA and protein expression was reported in patients with CD8 + CD16 + CD56phenotype 5,[9][10][11][12] . Consistently, we also found that the non-transformed cells, but is lost in malignancy, mostly has a consequence miR-146b promoter methylation, that prevents miR-146b expression even in the presence of constitutively activated miR-146b in T-LGL Leukemia patients STAT3 26,27 . Here we provide the first evidence of miR-146b promoter methylation at the expected sites, thus pointing that a similar mechanism might also take place in CD8 T-LGLL.…”
Section: Fasl Mrna-stabilizing Protein Hur Is Target Of Mir-146bsupporting
confidence: 84%
See 1 more Smart Citation
“…In particular, a significant increase in FasL mRNA and protein expression was reported in patients with CD8 + CD16 + CD56phenotype 5,[9][10][11][12] . Consistently, we also found that the non-transformed cells, but is lost in malignancy, mostly has a consequence miR-146b promoter methylation, that prevents miR-146b expression even in the presence of constitutively activated miR-146b in T-LGL Leukemia patients STAT3 26,27 . Here we provide the first evidence of miR-146b promoter methylation at the expected sites, thus pointing that a similar mechanism might also take place in CD8 T-LGLL.…”
Section: Fasl Mrna-stabilizing Protein Hur Is Target Of Mir-146bsupporting
confidence: 84%
“…In normal tissues STAT3 is reported to activate miR-146b transcription 24,25 . However, in several systems miR-146b promoter methylation has been shown to prevent miR-146b expression, even in the presence of constitutively activated STAT3 26,27 . According to the publically available methylome data (https://genome-euro.ucsc.edu/cgibin/hgTracks?db=hg19&lastVirtModeType=default&lastVirtModeExtraState=&virtModeType=def ault&virtMode=0&nonVirtPosition=&position=chr10%3A104196181-104196428&hgsid=230688991_Xz5zjxAjb58tIT5oL9i5MkaweCLp), four cytosine located miR-146b in T-LGL Leukemia patients upstream (-570bp, -63bp, -56bp, -26bp) and two located downstream (-71bp, and -273bp) the miR-146b TSS (Online Supplementary Figure S2) have been identified as differentially methylated in different cell lines.…”
Section: Mir-146b Is Differentially Expressed In Cd8 Vs Cd4 T-lgls Anmentioning
confidence: 99%
“…Affecting the miR-124/PTPN1 pathway could restore synaptic failure and memory deficits. Villela et al (2016) revealed that miR-124 is one of the most significantly dysregulated miRs in temporal cortex samples from patients with AD and predicted that dysregulation of miR-124 expression in the human brain may contribute to the pathogenic changes of AD (Villela et al, 2016). Aberrant activation of cyclin-dependent kinase-5 (CDK5) is mediated by calpain (CAPN)-induced cleavage of p35 into p25.…”
Section: Mir-124 In Neurodegenerative Disordersmentioning
confidence: 99%
“…In the temporal cortex of Alzheimer’s disease (AD) patients, a profile of six miRNAs involved in the regulation of a myelination pathway were found to be downregulated by hypermethylation of their CpG sites (Villela et al, 2016). Additionally, the miR-34a gene has been shown to be hypermethylated in ovarian cancer cells, indicating that its downregulation through epigenetics could promote the cancerous phenotype of the cells (Schmid et al, 2016).…”
Section: Mirna Synthesis/actionmentioning
confidence: 99%
“…Additionally, DNA methylation in the temporal cortex has been shown to directly target the CpG islands of miRNAs (Villela et al, 2016). By modulating the expression of regulatory miRNAs in the cortex, DNA methylation constitutes a process that can bring about an aging phenotype as seen in cells affected by Alzheimer’s disease.…”
Section: Mirna Synthesis/actionmentioning
confidence: 99%